Assessing sustainability of Lifestyle Education for Activity Program (LEAP) - Saunders, R. P. (Oxford University Press, 2012)
Sustained intervention effects are needed for positive health impacts in populations; however, few published examples illustrate methods for assessing sustainability in health promotion programs. This paper describes the methods for assessing sustainability of the Lifestyle Education for Activity Program (LEAP). LEAP was a comprehensive school-based intervention that targeted change in instructional practices and the school environment to promote physical activity (PA) in high school girls. Previous reports indicated that significantly more girls in the intervention compared with control schools reported engaging in vigorous PA, and positive long-term effects on vigorous PA also were observed for girls in schools that most fully implemented and maintained the intervention 3 years following the active intervention. In this paper, the seven steps used to assess sustainability in LEAP are presented; these steps provide a model for assessing sustainability in health promotion programs in other settings. Unique features of the LEAP sustainability model include assessing sustainability of changes in instructional practices and the environment, basing assessment on an essential element framework that defined complete and acceptable delivery at the beginning of the project, using multiple data sources to assess sustainability, and assessing implementation longitudinally.